2007
DOI: 10.1002/elps.200700277
|View full text |Cite
|
Sign up to set email alerts
|

Rapid sample screening method for authenticity controlling vanilla flavors using a CE microchip approach with electrochemical detection

Abstract: Five vanilla-related flavors of food significance, vanillic alcohol (VOH), ethyl maltol (EMA), maltol (MAL), ethyl vanillin (EVA) and vanillin (VAN), were separated using CE microchips with electrochemical detection (CE-ED microchips). A +2 kV driving voltage for both injection and separation operation steps, using a borate buffer (pH 9.5, 20 mM) and 1 M nitric acid in the detection reservoir allowed the selective and sensitive detection of the target analytes in less than 200 s with reproducible control of EO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…In this study, it was found that some of the methods that were suggested for routine application were used to analyze a low number of samples (e.g. n 5 12) [55][56][57][58]. Nowadays, HPLC is the most popular technique to determine biogenic amines in different food samples.…”
Section: Ce)mentioning
confidence: 96%
See 1 more Smart Citation
“…In this study, it was found that some of the methods that were suggested for routine application were used to analyze a low number of samples (e.g. n 5 12) [55][56][57][58]. Nowadays, HPLC is the most popular technique to determine biogenic amines in different food samples.…”
Section: Ce)mentioning
confidence: 96%
“…Also, it is desirable that studies involving the demonstration of food authenticity or adulteration include a large number of samples to be analyzed to validate the methodology. In this context, only in two of the analytical methodologies that are shown in Table 3 [45][46][47][48][49][50][51][52][53][54][55], the number of samples analyzed is significantly high (over 50 samples) [47,50].…”
Section: Food Authenticity or Adulterationmentioning
confidence: 98%
“…Because of the acid-base properties of target fingerprint markers, CZE was properly chosen. Previously optimized conditions (pH, ionic strength, and separation voltage) [28] were carefully adjusted to include in one fast run the separation of all fingerprint markers required for confirmation of frauds. Critical chemical conditions with a pH value of 9.5 and a 10 mM as borate concentration were finally selected as the best values on regarding both, separation times and resolution.…”
Section: Amperometric Detectionmentioning
confidence: 99%
“…However, other recent studies have only been devoted to the determination of prominent VAN and PHB [26], or VAN and EVA [27,28]. Indeed, we have previously proposed the separation of EVA and VAN using microchip format in presence of other food enhancers [28]. Nevertheless, this separation did not resolve the problem concerning confirmation of natural origin of the frauds since the confirmation of its natural origin needs the detection of other analytes such as PHB, VANA, and PHBA.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation